Overview of CERDIK Behavior in Diabetes Mellitus Clients at Posbindu Pakunden - Salsabilla, Dyas Fitriana; Rachmawati, Dewi; Mujito, Mujito (Health Access Journal, 2026)
Diabetes mellitus is a metabolic disorder caused by the pancreas not producing sufficient insulin or the body being unable to use insulin effectively, resulting in increased blood glucose levels, also known as hyperglycemia. The purpose of this study was to determine the description of CERDIK behavior among clients with diabetes mellitus. This study employed a descriptive research design. The sample consisted of patients diagnosed with diabetes mellitus within the last five years, with a total of 30 respondents selected using a purposive sampling technique. The research was conducted through a door-to-door approach in Pakunden Village, Sukorejo District, Blitar City. The results showed that all respondents (100%) had received information about diabetes mellitus. In the attitude category, more than half of the respondents (60%) demonstrated intelligent behavior. In the subjective norm category, more than half (57%) demonstrated intelligent behavior. Meanwhile, in the perceived behavioral control category, more than half of the respondents (57%) had correct perceptions. It can be concluded that the intention to engage in CERDIK behavior among clients with diabetes mellitus varies and still requires increased awareness regarding diabetes mellitus treatment and therapy in order to achieve better outcomes.